FeOOH Cocatalysts with Gradient Oxygen Vacancy Distribution Enabling Efficient and Stable BiVO4 Photoanodes - Wang, Shiyuan; Jiao, Mengjia; Ye, Qian; Jian, Jie; Li, Fan; Su, Guirong; Zhang, Lu; Zhang, Ziying; Ma, Zelin; Wang, Jiulong; Shuang, Yazhou; Wang, Fang; et al. (Nano-Micro Letters, 2026)
Highly active and stable FeOOH cocatalysts are essential for achieving optimal performance of BiVO4 (BVO) photoanodes. Despite offering remarkable structural stability, widely used thick FeOOH cocatalysts often suffer from insufficient hole transport capability, which hinders the overall activity. The present study demonstrates that a simple photoetching strategy is able to introduce gradient distributed oxygen vacancies (GOV) in the thick FeOOH layer and significantly enhances the photogenerated holes transport dynamics. The incorporation of GOV within FeOOH not only realizes the “relay transport” of photogenerated hole through the progressive upward shift of the valence band in the spatial distribution, but also provides abundant oxidation active sites by efficient hole trapping. These improvements effectively improve the oxygen evolution reaction (OER) activities and mitigate photocorrosion by the instantaneous hole extraction. Consequently, the FeOOH-GOV layer enables the BVO/FeOOH-GOV photoanode to achieve an impressive photocurrent density of 5.37 mA cm−2 and a robust operational stability up to 160 h at 1.23 VRHE, setting new benchmarks for current density and stability in FeOOH-based BVO photoanodes. This work provides an effective avenue to optimize OER cocatalysts for constructing highly efficient and stable photoelectrochemical water splitting devices. Highlights: 1 First demonstration of a gradient distributed oxygen vacancies (GOV) strategy to promote hole transport within FeOOH. 2 Clearly monitoring and verifying the progressive upward shift of the valence band within the shallow surface of FeOOH-GOv for enhancing holes transport capability. 3 Setting new photoelectrochemical activity and stability benchmarks of FeOOH based-BiVO4 photoanodes.